Review Article about Utilizing Renewable Energy in Medical Equipment - Abbas Abd, Ali Fadil; Abdalzahra, Muntadher Thamer; Abdel Razzaq, Namarek Hussein; Hassan, Malak Haider; Jwda, Ali Qaid Jeber (American Journal of Botany and Bioengineering, 2025)
Renewable energy sources such as wind, solar, hydropower, geothermal, and biomass are increasingly used to power medical equipment. The health sector can benefit from renewable energy on economic, health, and environmental grounds. For example, solar energy can ensure reliable, economical, and waste-free hospital power. However, the health sector often fails to take full advantage of renewable energy, highlighting a pressing opportunity to leverage these sources. Demand-side management can optimize hospital energy use, ensuring that critical loads such as surgical theatre lighting, vaccine cold chains, and essential medical equipment receive priority power allocation . Access to electricity is essential for improving economic and social welfare in rural areas. Globally, electrification reached 89% in 2017, up from 83% in 2010, yet almost 840 million people remain without access . The absence of proper medical facilities in rural settings contributes to high maternal mortality, which could be reduced by 70% with improved electrical access. Diesel generators are commonly used as backup power sources, but they are expensive and generate environmental pollution. Hybrid renewable energy systems incorporating solar, wind, and other resources represent a viable alternative for remote locations. These systems, modelled via comprehensive techno-economic and environmental analyses—often employing HOMER software—highlight the significance of operational costs, renewable fraction, and system optimization. Nonetheless, the power management of hospital loads has attracted limited attention. A grid-independent hybrid renewable energy system combined with demand-side management can satisfy both electrical and thermal hospital loads, offering an optimized configuration that meets healthcare energy requirements effectively.